The amount of Husk and Straw along with Rubber Tree Sawdust for Substrate to Culturing Bhutanese Oyster Mushroom (Pleurotus pulmonarius) - Phungbunhan, Karun; Intaravicha, Nuttakorn (Journal of Vocational Education in Agriculture, 2024)
This study investigated the use of different mixtures of Rice husk and rice straw, along with rubber tree sawdust, for the cultivation of Bhutanese oyster mushroom (Pleurotus pulmonarius) through a Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments included: 1. rubber tree sawdust 100%(control) 2. rubber tree sawdust 50 : rice husk 50% 3. rubber tree sawdust 80 : rice husk 20% 4. rubber tree sawdust 80 : rice straw 20% 5. rubber tree sawdust 33.3 : rice husk 33.3 : rice straw 33.3%. The results showed significant differences in mycelial growth, number of harvests, fresh weight, and length of stalk among the treatments. Treatment 2 (rubber tree sawdust 50: rice husk50%) exhibited the fastest full colonization time at 19.86 days, while Treatment 5 (rubber tree sawdust 33.3: rice husk33.3: rice straw 33.3%) took the longest at 22.91 days. Treatment 3 (rubber tree sawdust 80: rice husk20%) yielded the highest number of harvests, while Treatment 5 (rubber tree sawdust 33.3: rice husk33.3: rice straw 33.3%) yielded the least. For fresh weight, Treatment 3 (rubber tree sawdust 80: rice husk20%) had the highest yield, followed by Treatments 1, 4, 2, and 5 in descending order. Regarding the length of the stalk, Treatment 3 (rubber tree sawdust 80: rice husk20%) had the longest stalks, followed by Treatments 1, 4, 5, and 2. In conclusion, the study suggests that Bhutanese oyster mushroom can be cultivated using a substrate mixture of 80% rubber tree sawdust and 20% Rice husk or 100% rubber tree sawdust without significant differences in yield compared to using 100% rubber tree sawdust alone.